Comparision Effectiveness of Two Different Implant Surface Decontamination Methods by Surgical Treatment of Periimplantitis: A Clinical Trial - Elif Oncu; Bilge Can (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Objectives: The formation of bacterial biofilm on implant surfaces is the primary etiologic reason for peri-implantitis. The aim of this study is to present a new formulation including erythritol powder, which is widely used in air-polishing devices, and ultrasonic scaler with polyetheretherketone-coated tips, and to compare treatment effectiveness of them by comparison with conventional plastic scaler with 0.12% chlorhegxidine decontamination. Materials and methods: In this randomized, controlled study, 18 patients with peri-implantitis were included. A total of 40 dental implants were debrided with either ultrasonic instruments (test, n=20) or plastic scaler (control, n=20). Gingival recession depth (RD), keratinized tissue width (KTW), probing depth (PD), Gingival Index (GI) were evaluated at baseline and after 1 year. Supportive and nonsurgical periodontal therapies were firstly consulted to reduce the inflammation, before the surgical treatments of the defects. The formation of bacterial biofilm on implant surfaces was removed by standard plastic curettes, debridement made by combined 0.12% chlorhegxidinerinse or mechanical debridement made by ultrasonicpolyetheretherketone coated tips developed for implant surface and combined air-flow debridement.  Results: After 1 year healing period, PD, GI and PI levels of the patients in both group were significantly lower. Combined air-flow debridement and the mechanical debridement performed by using ultrasonic polyetheretherketone-coated tips were better at decreasing the level of periodontal pocket depth and plaque scores than plastic curettes. Conclusion: Ultrasonic driven instruments equipped with a special tip and airflow devices using erythritol powder seem to be a viable alternative to the traditional debridement of implants in periimplant mucositis.